THE INFLUENCE OF RECREATIVE SYNCHRONIZED SWIMMING ON MUSIC AND INTELLECTUAL FACTORS AND PERSONAL CHARACTERISTICS - Jadranka Kocić; Slađana Tošić; Dragana Aleksić; Dragan Toskić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Synchronized swimming is way of acivitie connected with music. Emotional character in it could be very efficiency mean of childs` and youth` sport-recreative activities. The research was lead on 60 girls 7-15 years old, elementary schools pupils in Niš, members "Sirene" Niš synchronized swimming clyb. Music abilities research was obtained using Seashore test for basic music abilities. For testing input procesors, perceptive reason, it was used IT-1 test. For testing efficiency parallel prosecor it was used S-1 test. For testing serial procesors, symbolic reason, it was used AL-4 test sinonime-atimime. For testing personal characteristics it was used instruments for testing dimensions of functional konnative regulatione mechanisms model. It was used bases statistics for every researcg area (music abilities, intellectual abilities, konnative characteristics and criteria variable); to estimate influence each predictor variable on criteria variable, it was used regression analysis. Results showed statistic efficiency in music and konnative factors. Synchronized swimming activities influence on growing spontaneous, independence developing, tense releases, and it is exellent area for emotional health and society desirable behaveour norm. These activities are reached by music, which in melodie and rithm diversity, gives complete enjoyment, and psychosisical relax and refreshment.